Pemanfaatan Card Game untuk Meningkatkan Minat Belajar Bahasa Inggris Siswa-Siswi Kelas 8 di SMP Negeri 2 Kaliwungu - Kisnanto, Yustina; Hapsari, Stepanie; Priskantya, Atalya; Anggraeny, Mutiara; Kusumastuti, Nathalie (Jurnal Pengabdian UntukMu NegeRI, 2024)
Fulfilling the English learning needs of junior high school students by using qualified teaching aids is not easy for English teachers in rural Indonesia. To overcome this obstacle, SMP Negeri 2 Kaliwungu Boyolali collaborated with a team of four students and one lecturer of PBI UKSW in the program "Visual Learning Aids for English Teaching in SMP Negeri 2 Kaliwungu." This community service program aims to help English teachers of SMP Negeri 2 Kaliwungu create effective and fun English learning by providing card game learning aids based on the needs analysis of the English teachers and students, especially Grade 8. This community service program generally consisted of four steps: preparation, interviewing, making teaching media, and evaluation, which included presenting the teaching media to the school and a game simulation with some students. The program evaluation results showed that the students could understand the story by arranging the sentences on the card game correctly, and the teacher was also satisfied with the alternative learning media because the attractive visuals on the cards could motivate students.